Iron-foam as a heterogeneous catalyst in the presence of tripolyphosphate electrolyte for improving electro-Fenton oxidation capability. (10th May 2018) - Deng, Fengxia; Garcia-Rodriguez, Orlando; Olvera-Vargas, Hugo; Qiu, Shan; Lefebvre, Olivier; Yang, Jixian
Abstract: Fe-Foam (Fe-F) was used as a catalyst in the presence of tripolyphosphate (TPP) electrolyte for electro-Fenton (EF) at circum-neutral pH. Characteristics of Fe-F catalyst were studied by scanning electron microscopy energy dispersive spectroscopy (SEM-EDS) and x-ray photoelectron spectroscopy (XPS). Operational conditions (pH and current) influencing H2 O2 electrogeneration in TPP electrolyte at a three-dimensional printed gas diffusion electrode (GDE) were systematically investigated. Moreover, linear sweep voltammetry was used to evaluate the system. Results showed that Fe-F, a three-dimensional porous structure catalyst, was covered with Fe 2+, Fe 3+ and Fe 0 . The Fe-F/TPP/EF process allowed an 8.55-fold increase in the rate of phenol degradation (used as a model pollutant), higher pseudo-first-order rate constants (6.22 × 10 −2 min −1 against 7.30 × 10 −3 min −1 ), a significantly higher mineralization yield (88.69%% against 30% after 8 h electrolysis) and lower energy consumption (0.10 kWhg −1 against 0.98 kWhg −1 ), as compared to conventional EF process. The high efficiency in Fe-F/TPP/EF was attributed to the following benefits: i) Fe-F was capable of providing Fe 2+ ions by chemical corrosion to form Fe 2+ -TPP complex, which induced the one-electron transfer activation of O2 leading to formation of OH, ii) chemical Fe 2+ regeneration combined with Fe 0 corrosion provided an additional source of Fe 2+ and compensated the low capacity of Fe 3+ reduction at GDE, and iii) both surface-mediated and homogeneous reactions contributed to pollutant degradation. The new proposed Fe-F/TPP/EF process displayed promising properties for wastewater treatment applications. Graphical abstract: Highlights: Iron-foam (Fe-F) is the first time used in electro-Fenton (EF) with tripolyphosphate (TPP) electrolyte (Fe-F/TPP/EF). The Fe-F/TPP/EF process can be operated at near circum-neutral pH. Surface-catalyzed mechanism and homogeneous reactions are involved in Fe-F/TPP/EF.